As representações da infância na mídia impressa em Mato Grosso nos anos de 1930 a 1945 : o tripé família, educação e saúde - Oliveira, Ozéas de (2013)
The Brazilian infancy is a privileged area of social intervention in the first half of the 20th century, moment in which public policies are formed to provide service for it. This research focuses on the infancy representations in newspapers and in magazines, that were in circulation in Mato Grosso, from 1930 to 1945, with the objective of understanding how determining conceptions of infancy become leading of public policies focusing on the child and its service. This is, in the context of the state of Mato Grosso, to analyze how the infancy is taken over by the policy actions, as the social intervention area, in a way that phenomenons relative to the infant population become categorized, measured and prescribed by making this time of life a target for power technologies. For theoretical foundation, we have contributions of Michel Foucault, Phillippe Ariès, Roger Chartier e Norbert Elias, whose most important analytic tools for this research are, respectively: the infancy as historic and cultural construction, the concept of representation and of civilized process. This is, therefore, a historic research, based on the cultural history, that has as sources the newspapers that were in circulation between the years of 1930 and 1945, like “O Estado de Mato Grosso” (The State of Mato Grosso), “A Cruz” (The Cross), and the diverse magazine from the city of Cuiabá “ A Violeta” (The Violet), the newspaper that had significant circulation in Mato Grosso and was a product of the Grêmio Literário Feminino “Júlia Lopes de Almeida”, institution of great importance in the literacy and intellectual life of the capital and the state. We have observed how the infancy representations are crossed over by a strong concern with the future of the nation and its development, that, on the other hand, is materialized in the policies of assistance and of education for children, related to a national policy plentiful in agreement with the ideals and aspirations of, the Vargas Government, as a construction of the “new Brazilian man”, the development of the nation and the strengthening of the state.